Antimicrobial peptides for combating drug-resistant bacterial infections. (May 2023) - Xuan, Jiaqi; Feng, Weiguo; Wang, Jiaye; Wang, Ruichen; Zhang, Bowen; Bo, Letao; Chen, Zhe-Sheng; Yang, Hui; Sun, Leming
Abstract: The problem of drug resistance due to long-term use of antibiotics has been a concern for years. As this problem grows worse, infections caused by multiple bacteria are expanding rapidly and are extremely detrimental to human health. Antimicrobial peptides (AMPs) are a good alternative to current antimicrobials with potent antimicrobial activity and unique antimicrobial mechanisms, which have advantages over traditional antibiotics in fighting against drug-resistant bacterial infections. Currently, researchers have conducted clinical investigations on AMPs for drug-resistant bacterial infections while integrating new technologies in the development of AMPs, such as changing amino acid structure of AMPs and using different delivery methods for AMPs. This article introduces the basic properties of AMPs, deliberates the mechanism of drug resistance in bacteria and the therapeutic mechanism of AMPs. The current disadvantages and advances of AMPs in combating drug-resistant bacterial infections are also discussed. This article provides important insights into the research and clinical application of new AMPs for drug-resistant bacterial infections.